Becoming-animal in the Chinese Martial Arts - Farrer, Douglas (Living Beings, 2020)
This chapter examines Chow’s Family Southern Praying Mantis to delineate a field of action involving animals and humans, where humans develop secret powers of the body derived from observation and self-experimentation combined with centuries of embodied—not just oral—transmission. For Deleuze and Guattari becoming is rhizomic; it does not depend on systems of a scientific classification or genealogy. Martial performance ethnography is where the researcher joins in and learns a martial art. Chow Gar comprises a method for the development and transmission of deadly martial skills. Legend has it that Chow Gar emerged from the Fukien Shaolin Temple, which was destroyed when the monks became involved in the revolutionary uprisings against the Ming Dynasty. Chow Gar develops the hidden or dark powers including sharp eyesight, strong bones, iron fingers, flexible sinews and extraordinary strength, all trained through sweat, blood and breath. According to oral history, Wong Fook Go possessed black fingertips like steel talon